BEST PRACTICE PENDIDIKAN KARAKTER PADA LEMBAGA PENDIDIKAN BERBASIS AGAMA: PENGALAMAN PONDOK PESANTREN AL-WAHDAH - Setiabudi, Muharyadi Tri Yuli; Kurniawati, Putri Indah; Muthoharoh, Muthoharoh (Solidarity: Journal of Education, Society and Culture, 2012)
Religious education can be a very effective means to educate character education. The purpose of this research is to explain the application and the results of character education in Pondok Pesantren Al Wahda. This research uses qualitative research method in which which the data are collected through interview, observation, and documentation. The research shows that that character education in pesantren is applied through modelling, rule, and direct instruction. All of that models are applied in three areas: learning and teaching process, tha habits of student in pondok pesantren, and students activity outside pesantren. The value taught is based on kitab very specific to pesantren. The result of character education can be observed through students behavior and habit which naturally develop from long process of internalization.